Beneath the skin : (in)visible inscriptions Marele Day's The disappearances of Madelena Grimaldi - P. Sant; J. Brown (Law Text Culture, 1995)
In The Disappearances of Madalena Grimaldi, the latest thriller by Shamus-award winner Marele Day, Sydney is a gothic landscape where nothing is as it seems. Hence this view of her living city: The surface of the city is merely a skin. Beneath it are the veins carrying life blood, air vents that act as lungs, the sewers a lymphatic system draining away waste products, telephone lines the nervous system transmitting messages for the proper functioning of the body (p. 148). All functions are not benign, but Day's wicked humour persists. Her chameleon Private Investigator, Claudia Valentine, is again severely tested, not least because she is personally and psychologically connected to her new investigations.